Female genital cutting and the politics of Islamicate practices in Egypt : debating development and the religious/secular divide - Van Raemdonck, An (Afrika focus, 2016)
My PhD dissertation examined discourses on Female Genital Cutting (FGC) in contemporary Egypt, particularly concerning the relation between FGC and religion. FGC is practiced by both Muslims and Christians and Egypt is among the countries with the highest prevalence rates. Through ethnographic research, the study analysed the vernacularization of transnational activism as an important intervention into local cultural and social debates on gender, sexuality and family norms, in addition to understandings of Islam, Muslim-Christian relations and concepts of race, nation and progress. I argue that FGC is best characterized as an Islamicate practice. A narrow, reifying conceptualization of religion precludes lived understandings of the relation of FGC to Islam and subsequently, precludes more profound social and cultural debate on gendered practices. Key words: FGC, religion, Islam, Egypt, critical development studie